Manolis Korres. The Odeion Roof of Herodes Atticus and other Giant Spans. - Russell, Ben (Journal of Greek Archaeology, 2017)
The Odeion of Herodes Atticus, built between AD 160 and 169, is a looming hulk of a structure. It could have housed, at a reasonable estimate, around 6000 spectators. Despite its size and relatively good state of preservation, the building remains something of an enigma. In particular, the thorny issue of whether it was roofed, open-air, or partially covered in some way has rumbled on for well over one hundred years. Any roof would have had to cover a space measuring c. 83m east-west and c. 56m north-south, which would make it the largest roof span known from antiquity. Undeterred by the staggering scale of the undertaking, Manolis Korres here presents his case for a roof. In this beautifully put together, stunningly illustrated volume, Korres combines careful study of the structural remains with detailed discussion of the practicalities of creating a roof of this scale. It would take a structural engineer to provide a full appraisal of many of the more technical aspects of Korres’ reconstruction and so, in what follows, I will focus primarily on his archaeological and architectural observations.